1975
DOI: 10.1159/000275228
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic Effusions in Children – Some Parameters Involved

Abstract: A retrospective analysis of 1,078 adenoidectomies and 660 adenotonsillec-tomies in children under the age of 11 is reported, special attention having been paid to the presence of tympanic effusions. Eight parameters involved were recorded and analyzed. Amongst other things, it appeared that in adenoidectomy patients referred to the author transient tympanic effusions were very common (i.e. in 41.8 % of the 2,156 ears) and that adenoid size and eosinophilia did not have any relation with these effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Ferrer (1974), in a case-control study, found no association between glue ear and a previous history of atopy. Wind (1975), in a retrospective analysis of over 2,200 myringotomies, found that the presence of middle-ear effusions was not associated with eosinophilia. Similar conclusions were drawn by Reisman and Bernstein (1975) from a series of 200 glue ear cases-23 per cent gave a history of atopy, a similar proportion to the general population.…”
Section: (7) Allergymentioning
confidence: 98%
See 2 more Smart Citations
“…Ferrer (1974), in a case-control study, found no association between glue ear and a previous history of atopy. Wind (1975), in a retrospective analysis of over 2,200 myringotomies, found that the presence of middle-ear effusions was not associated with eosinophilia. Similar conclusions were drawn by Reisman and Bernstein (1975) from a series of 200 glue ear cases-23 per cent gave a history of atopy, a similar proportion to the general population.…”
Section: (7) Allergymentioning
confidence: 98%
“…Thus, after some sixty years' consideration of allergy, there is still doubt as to its aetiological role in glue ear. been removed; and Wind (1975) noted that in Holland myringotomy is the standard treatment for acute otitis media and yet glue ear is common. To date, there has been no clear evidence to support the lack-of-surgery theory.…”
Section: (7) Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many children with glue ear have never received antibiotics for suppurative otitis media,5 and in Holland, where the latter condition is commonly treated by myringotomy rather than antibiotics, glue ear apparently occurs commonly. 6 Messrs Slack and Drake-Lee also argue that the social class differences in the rate of surgery for glue ear are a true reflection of levels of need. They suggest that children in social class V "have a higher incidence of chronic ear disease" than those in social class I.…”
Section: David Jobsonmentioning
confidence: 99%